Non-cystic-fibrosis bronchiectasis in children: A persisting problem in developing countries - KARADAĞ, BÜLENT TANER (KARGER, 2005)
Background: Non-cystic-fibrosis (non-CF) bronchiectasis in childhood is still one of the most common causes of childhood morbidity in developing countries. The management of these patients remains problematic, and there are few studies of long-term outcome. Objective: The aim of this retrospective study was to define the general characteristics, underlying causative factors and long-term follow-up results of non-CF bronchiectasis patients. Methods: One hundred and eleven consecutive children, diagnosed with non-CF bronchiectasis were included in the study. General characteristics and underlying causes were recorded from the medical records. Clinical outcomes were evaluated in terms of lung function tests, annual exacerbation rates and patient/parent perception of health status. Results: Mean age of the patients was 7.4 +/- 3.7 years at presentation, and patients had been followed 4.7 +/- 2.7 years on average. In 62.2% of the patients, an underlying etiology was identified, whereas postinfectious bronchiectasis was the most common (29.7%). In spite of intensive medical treatment, 23.4% of the patients required surgery. The annual lower respiratory infection rate has decreased from a mean of 6.6 +/- 4.0 to 2.9 +/- 2.9 during follow-up ( p < 0.0001). Lung function tests were also found to be improved (mean FEV1 % 63.3 +/- 21.0 vs. 73.9 +/- 27.9; p = 0.01; mean FVC% 68.1 +/- 22.2 vs. 74.0 +/- 24.8; p = 0.04). There was clinical improvement in both the surgical (73%) and medical (70.1%) groups ( p > 0.05). Conclusion: In conclusion, bronchiectasis remains a disease of concern to pediatricians, particularly in developing countries. Infections are still important causes of bronchiectasis, and clinical improvement can be achieved by appropriate treatment. Although medical treatment is the mainstay of management, surgery should be considered in selected patients. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: children; bronchiectasis; management; SPUTUM; DISEASE; CT